Dematerializzazione dei dati ed e-Government. Problemi e prospettive per l’informatica giuridica - D'Avanzo, Wanda (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2022)
The issue of digitization is complex and vast because it implies the reference to various fundamental concepts for the legal sciences: governance, organizational and management strategies, data management and increasingly sophisticated technologies, the problem of training the jurists of the future. In the European strategy, the potentialities inherent in the management of digital data and the most advanced technologies are evaluated as a fundamental factor in pursuing the main sustainable development goals of the coming years. In the public sector, in particular, the digital transition represents a fundamental field of application, of specific interest for legal informatics.